Literature Review: Faktor yang Mempengaruhi Kejadian Speech Delay pada Anak - Cholilah, Mila; Kholifah; Endang Kartiasih; Vivi Ulviningsih; Any Sugesti; Siti Apriyati; Mudrikah; Kurniawati Tri Utami; Defri Novitasari; Dian Wijayati; Sofiyanti, Ida (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Speech delay is the most common disorder in children and causes anxiety for parents. The purpose of this literature review is to determine the factors that influence the incidence of speech delay in children. This literature review is through searching the results of publications on the  Google Scholar database, and the Garuda Portal between 2020-2024. The keywords used were factors AND speech delay AND children. Search for articles related to 6 sources that are included in the inclusion criteria. It was concluded that internal factors affecting the incidence of speech delay in children are physical disability, gender and premature birth. External factors that influence the incidence of speech delay are parenting, lack of communication between parents and children, maternal education, family economy, and gadget use. Parents can increase stimulation and communication in children, and utilize speech therapy in health facilities.   Abstrak Speech delay merupakan gangguan yang paling sering terjadi pada anak dan menyebabkan kecemasan bagi orang tua. Tujuan literature review ini adalah untuk mengetahui faktor-faktor yang mempengaruhi kejadian speech delay pada anak. Literature review ini melalui penelusuran hasil-hasil publikasi pada database Google Scholar, dan Portal Garuda antara tahun 2020-2024. Kata kunci yang digunakan yaitu faktor-faktor dan speech delay dan anak. Penelusuran artikel yang terkait 6 sumber yang termasuk dalam kriteria inklusi. Kesimpulannya bahwa faktor internal yang mempengaruhi kejadian speech delay pada anak adalah kecacatan fisik, jenis kelamin dan kelahiran prematur. Faktor eksternal yang mempengaruhi kejadian speech delay adalah pola asuh orang tua, kurangnya komunikasi orang tua dan anak, pendidikan ibu, ekonomi keluarga, dan penggunaan gadget. Orang tua  dapat meningkatkan stimulasi dan komunikasi pada anak, serta memanfaatkan terapi wicara di fasilitas kesehatan.